Decolonising restorative justice: a case of policy reform - Levers, Leanne Alexis (Routledge, 2024)
This book critically examines the colonial dimensions of restorative justice through the lens of justice policy reform in Jamaica. Restorative justice is not new. Practices of restitution can be found throughout history, predominantly in non-western traditions and religions. One of the key principles of restorative practices is that of contextualisation. That is, restorative practices are developed and embedded within the political, economic, and cultural context of the communities in which they are practiced. Many of the countries that have gone on to develop restorative justice as part of their formal justice system have developed their policy on the model of their indigenous communities - for example, in Canada and in New Zealand. However, with the globalisation of restorative practices within the past decade, many countries have sought to 'colonize' restorative justice, by developing a standardized, best practice approach. Instead of a practice that is developed and formed by its community, colonized restorative justice dictates that one-size-fits all. Examined through the lens of the development and implementation of restorative justice policies in Jamaica, this book argues that this westernised approach diminishes the effectiveness of restorative justice in its capacity: to address the victim's needs; to hold the offender accountable in a way that reintegrates them into society; and to empower the community by involving them in the provision of justice to victims. Restorative justice, then, must be decolonized - and local, indigenous, practices acknowledged - if it is to achieve its aims. This book will be of interest to a range of scholars with interests in decolonization, as well as alternative dispute resolution; and especially those in sociolegal studies, criminology, human rights, social policy, political science, and Caribbean studies